Physical characteristics, morphology and protein profiles of salivary glands of two local edible nest swiftlet species - Ibrahim, Muhammad Marwan (2016)
In the age of twenty centuries, edible bird nest (EBN) was highly contributed towards most of the Asian countries economy. However, as the EBN is constructed from saliva of the swiftlet, association between the nest and the salivary glands is still obscure. This is a fundamental study providing valuable information about the salivary glands of EBN swiftlets. The first objective of this study was to compare the morphological characteristics of Malaysia’s EBN swiftlets and examination of the histomorphology of the salivary glands. The second objective which is the main part of the study was to profile and identify the difference in protein spots from the salivary glands of EBN swiftlets. The last objective was to profile the glycoproteins of EBN swiftlets salivary gland using lectin based detection method. A total of 20 birds were caught in the Gomantong Cave, Sabah, out of which, 10 of it were A. fuciphagus and the balance were A. maximus. Both species were compared morphologically and it shows that A. maximus are larger in body size compared to A. fuciphagus. The sublingual gland on the other hand shows that, both species have morphologically similar including the size. The tissue was then stained with H&E stain and results show that both species generally have quite similar tissue structure. Combination of Alcian Blue-Periodic Acid Schiff shows both species are rich in mixture of acidic and neutral mucins secretion. However, A. fuciphagus has greater neutral mucin secretion compared in A. maximus. Based on relative sublingual glands weight, comparison between female A. fuciphagus and female A, maximus are the only one that shows significantly difference. Proteomics studies commenced with the protein quantification and A. fuciphagus male has the highest concentration of protein which is 8.675 μg/μL followed by A. fuciphagus female 6.875 μg/μL, while in male and female A. maximus consist of 5.743 and 6.117 μg/μL of proteins respectively. 2D gel was performed to obtain the salivary gland protein profiles and the differential proteins expressed were identified using LC/MS Q-ToF mass spectrometry analysis. Profiling of the glycoproteins shows most of the glycoproteins present are the N-link glycoproteins and conjugated with sialic acid.